2020
DOI: 10.1038/s41467-020-16639-1
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a multi-valent human papillomavirus vaccine by capsomere-hybrid co-assembly of virus-like particles

Abstract: The capsid of human papillomavirus (HPV) spontaneously arranges into a T = 7 icosahedral particle with 72 L1 pentameric capsomeres associating via disulfide bonds between Cys175 and Cys428. Here, we design a capsomere-hybrid virus-like particle (chVLP) to accommodate multiple types of L1 pentamers by the reciprocal assembly of single C175A and C428A L1 mutants, either of which alone encumbers L1 pentamer particle self-assembly. We show that co-assembly between any pair of C175A and C428A mutants across at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Due to the lack of protein glycosylation and the formation of inclusion bodies in prokaryotic expression systems, most vaccine development efforts targeting SARS-CoV-2 have focused on mammalian expression systems instead of the highly efficient E. coli system. 5 , 36 However, studies have reported successful development of antiviral vaccines with the use of E. coli for expression, such as the expression of virus-like particle (VLP) structures of human papillomavirus (HPV) and hepatitis E virus (HEV) 37 , 38 and the use of OMVs to deliver viral antigens of dengue virus, influenza virus, and Middle East respiratory syndrome (MERS) coronavirus. 11 , 39 , 40 Therefore, when using an E. coli expression system, vaccines should form stable polymers and regular nanostructures, and RBD-BBVs designed by us meet those requirements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to the lack of protein glycosylation and the formation of inclusion bodies in prokaryotic expression systems, most vaccine development efforts targeting SARS-CoV-2 have focused on mammalian expression systems instead of the highly efficient E. coli system. 5 , 36 However, studies have reported successful development of antiviral vaccines with the use of E. coli for expression, such as the expression of virus-like particle (VLP) structures of human papillomavirus (HPV) and hepatitis E virus (HEV) 37 , 38 and the use of OMVs to deliver viral antigens of dengue virus, influenza virus, and Middle East respiratory syndrome (MERS) coronavirus. 11 , 39 , 40 Therefore, when using an E. coli expression system, vaccines should form stable polymers and regular nanostructures, and RBD-BBVs designed by us meet those requirements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…E. coli is the most productive and least costly protein expression system. Vaccines against SARS [ 35 ], dengue fever [ 29 ], Middle East respiratory syndrome [ 36 ], hepatitis E [ 37 ], influenza [ 38 ], and human papillomavirus [ 39 ] have been successfully expressed as nanostructures in E. coli . Therefore, the correct folding or assembly of viral antigens into nanostructures in E. coli could elicit potential immune protection, thus enabling the successful development of an inexpensive vaccine in E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are developing PCR tests to detect more HPV genotypes [31] and are proposing methods to produce vaccines that can prevent HPV of other genotypes. [48] Currently, some genotypes with the highest infection rates in Canada are not targeted by PCR tests or vaccines. We recommend a better alignment of the genotypes targeted by HPV tests and vaccines with those genotypes with the highest infection rates in Canada.…”
Section: Discussionmentioning
confidence: 99%